REGENerasi: Renewable bioenergy technology based on anaerobic fermentation and IoT from corn and straw waste to address the energy crisis for farmers in the era of climate change - Mahmudi, Gilang Arya; Bagaskoro, Satria; Lestari, Dwi Puji (EcoVision: Journal of Environmental Solutions, 2026)
Background: Indonesia, as an agrarian country, faces a major challenge in the form of an energy crisis within the agricultural sector, increasingly exacerbated by climate change. Approximately 62% of agricultural energy demand in Indonesia still relies on conventional methods, while irrigation energy requirements continue to rise by an average of 15% per planting season in drought-prone areas. Consequently, 64% of farmers report energy cost increases exceeding 20%, and 27% experience partial crop failures, posing a threat to national food security. To address these challenges, this study proposes an innovation called REGENerasi: a renewable bioenergy technology based on anaerobic fermentation and the Internet of Things (IoT), utilizing corn and straw waste. Methods: This study employs a literature-based analytical approach to explore the potential of integrating anaerobic fermentation reactors with IoT sensors for efficient bioenergy production. The anaerobic fermentation process converts lignocellulosic agricultural residues particularly corn cobs and straw containing 32–40% cellulose, 25–30% hemicellulose, and 15–20% lignin into biogas (methane), biochar, and liquid fertilizer within a multi-integrated system. IoT-based monitoring and control systems were theoretically assessed for their capacity to enhance biomass conversion efficiency and energy savings. Findings: The literature review reveals that IoT integration in anaerobic fermentation systems can improve biomass conversion efficiency by up to 35% and reduce energy consumption by 20%. The use of high-lignocellulose agricultural waste, such as corn and straw residues, provides a sustainable substrate for biogas production. The proposed system has potential to generate thermal and electrical energy while simultaneously producing biochar and organic fertilizer, creating a circular and environmentally friendly agricultural energy model. Conclusion: This bioenergy innovation strengthens farmers’ energy independence and contributes to climate change mitigation and adaptation strategies. It aligns with Sustainable Development Goal (SDG) 13 Climate Action by promoting local renewable energy solutions within the agricultural sector. Novelty/Originality of this article: The novelty of this research lies in the development of an adaptive renewable bioenergy system that integrates anaerobic fermentation with IoT technology using corn and straw waste as substrates. This multi-integrated model offers a new pathway for sustainable energy generation and circular resource management in rural agricultural communities, particularly in East Java, Indonesia.